STudy on E-Cigarettes and Pregnancy (STEP) – Study Protocol of a Mixed Methods Study on Risk Perception of E-Cigarette Use During Pregnancy and Sample Description - Schilling, Laura; Schneider, Sven; Maul, Holger; Spallek, Jacob (Geburtshilfe und Frauenheilkunde, 2020)
Introduction During pregnancy, the motherʼs healthy lifestyle is crucial for the health of the fetus. Potential risk factors for maternal and child health should therefore be identified and reduced as early as possible. The consumption of e-cigarettes represents one of these potential risk factors. Exploring risk perceptions about e-cigarette use during pregnancy can provide early indications of possible user motives. Therefore, our mixed methods STudy on E-cigarettes and Pregnancy (STEP) aimed to comprehensively analyze risk perceptions about e-cigarette use during pregnancy based on an Integrated Health Belief Model (IHBM). This paper describes the study design, methods, sample population and limitations of STEP.Methods Our sequential mixed methods study combined qualitative and quantitative approaches. In the qualitative section of the study which preceded the quantitative part of the study, we aimed to characterize risk perceptions about e-cigarette use during pregnancy. We used a netnographic research approach which analyzed discussion threads in online forums dealing with e-cigarette use during pregnancy. The analysis was based on an IHBM. Identified themes were incorporated in the questionnaire which was developed for the quantitative part of the study. The quantitative section aimed to quantify, among other things, perceived threats, barriers and benefits and to explore differences in risk perception according to sociodemographic characteristics and tobacco and e-cigarette usage.Results In the qualitative section, 1552 posts in 25 online discussion threads dealing, inter alia, with e-cigarette use during pregnancy were identified. The quantitative part looked at the responses in the questionnaires handed in by 575 pregnant women who attended a hospital in Hamburg (Germany) from April 2018 to January 2019 (response rate: 27.5%).Conclusion Data collection was successful for both the qualitative and quantitative parts of the study. When interpreting the results of STEP, different limitations should be taken into account. The results of STEP provide starting points for the development of tailored preventive measures for pregnant women.
Keywords: e-cigarette; pregnancy; risk perception; mixed methods study; Health Belief Model